PENGARUH KOMPETENSI WIRAUSAHA, PEMBINAAN USAHA DAN INOVASI PRODUK TERHADAP PERKEMBANGAN USAHA (Studi Pada Usaha Kecil dan Menengah Batik di Sentra Pesindon Kota Pekalongan) - Yully Christiana; Ari Pradhanawati; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2014)
This study aims to determine the influence of  entrepreneurial competence, business development service, product innovation to business development Batik SMEs. This type of research is explanatory research, with methods data collection using questionnaires and interviews. Sampling techniques using the technique samples are saturated. The sample in this research were 36 businessmen Batik on Pesindon Sentra. This research uses techniques of quantitative analysis. Quantitative analysis using the test of validity, reliability, regression analysis, the determination coefficient, and test of significance (t-test).From the data analysis it can be conclude, that the indicate below entire partially independent variable, the variable entrepreneurial competence (X1) effect on business development (Y) amounted to 77,7%, business development service (X2) effect on (Y) business development of 23,9%, and product innovation (X3) effect on business development (Y) of 66,5%. Some suggestions are recommended from this research is the related agencies need to conduct integrated socialization and training on understanding financial statements, reactivate the Pesindon media telecenter, conduct training on the management of capital, evaluation at any development activities, introduce new technologies to help SMEs in managing their business.